THE RELEVANCE OF ARABIC LANGUAGE IN ISLAMIC STUDIES PROGRAM: A CASE STUDY OF OPEN UNIVERSITY MALAYSIA (OUM) - Hamidah Mat; Wan Ubaidillah Wan Abas (2016)
Numerous studies have been carried out to identify the relevance of Arabic language to Islamic studies subjects. As a medium of communication like other languages, Arabic has its own function in conveying Syariah knowledge. This is mainly because Arabic is the language of the Holy Quran and Sunnah, which are the primary sources of Islam. This study attempts to analyze the relevance of learning the Arabic language amongst Open University Malaysia (OUM) students. This research involves students of two programs in OUM, Bachelor of Islamic Studies and Diploma in Islamic Studies. A survey was conducted to identify a relationship between student’s Arabic language proficiency and their learning process on courses taught. It is also intended to know student’s perception on the relevance of Arabic language to Islamic studies courses. The study found that most respondents agree on the importance of mastering the Arabic language in Islamic studies. [Abstract by authors]